Pan is Not in Danger at UWI - Gibbons, Rawle (Trinidad Express)
In a letter to the editor, Rawle Gibbons seeks the clarify the statement made by Pat Bishop in her address at the University graduation ceremony, which stated that “...not one single graduate of 1994 has qualified in any serious steel drum concern”. Rawle argued that there were programmes in steelpan on the University curriculum.
Keywords: Bishop, Pat (Patricia Allison); Steel bands (Music) -- Education -- Trinidad and Tobago; Music -- Instruction and study -- Trinidad and Tobago; Steel drum (Musical instrument) -- Trinidad and Tobago